Critical Reading and The Ability to Uncover The Implicit Meanings of Short Story Text of Middle School Students - Mardiana Mardiana; Mayong Maman; Sultan Sultan (ppjbsip, 2019)
This study aims to: (1) describe the ability of student to uncover the implicit meaning of short stories before applying critical reading strategies in grade VII student of Marioriawa State Middle School 3 Soppeng Regency; (2) describe the ability of student to uncover the implicit meaning of short stories after applying critical reading strategies in grade VII student of Marioriawa State Middle School 3 Soppeng Regency; and (3) knowing the effect of critical reading strategies on the ability to uncover the implicit meanings of short story texts in class VII students of Marioriawa 3 Public Middle School, Soppeng District. This type of research is quantitative research with a pre-experimental design using test techniques namely the initial test (pretest) and the final test (posttest). The sample of this study was the seventh grade students of Marioriawa State Middle School 3 Soppeng Regency, amounting to 45 people. The data collection technique used is the test technique. The results showed that there was a significant effect of critical reading on the ability to express the implicit meaning of short stories.